THE INFLUENCE OF INTEGRATED MARKETING COMMUNICATION AND INSTAGRAM SOCIAL MEDIA IN IMPROVING BRAND IMAGE AT KOPI LADANG - Yudha Yustiasa; Endang Sulistya Rini; Evawany Yunita Aritonang (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The development of digital technology has encouraged companies to integrate marketing communication strategies through various channels, including social media. This study aims to analyze the effect of integrated marketing communication (IMC) and the use of Instagram social media on improving brand image in the local brand Kopi Ladang. The study used a quantitative approach with a survey technique on 140 respondents who were active followers of the Instagram account @kopiladang.id. IMC variables include advertising, sales promotion, direct marketing, public relations, and digital marketing, while social media variables focused on interaction intensity, content quality, and user engagement. The results of multiple regression analysis show that there is a positive impact between Integrated Marketing Communication on Brand Image in Kopi Ladang, There is a positive impact between Kopi Ladang Instagram Media on Kopi Ladang Brand Image, There is a significant relationship between Integrated Marketing Communication and Instagram Media on Brand Image in Kopi Ladang and There is an Influence between Integrated Marketing Communication on Brand Image through Instagram Social Media, namely between Integrated Marketing Communication and Instagram Social Media has a significant impact on Brand Image in Kopi Ladang. Instagram social media acts as a medium between Integrated Marketing Communications, showing how influential the level of Instagram Social Media among customers can be in increasing Brand Image in achieving a more significant influence.